Improving digital financial literacy for investment decision making in Padangsidimpuan City through the Analytic Hierarchy Process (AHP) method - Khairunnisa Al Madany; Rizaldy Khair; Nirmalahaty Harahap; Wisnu Yudhistira (Borneo Novelty Publishing, 2025)
In today's digital era, digital financial literacy plays an important role in shaping people's investment behavior and decisions. Padangsidimpuan City, one of the cities in Indonesia, faces challenges in adopting and implementing digital financial literacy among its citizens. Effective and efficient investment decision-making is crucial in the current economic context, where financial information is widely available but often complex and difficult for the general public to interpret. The application of digital financial literacy can improve individuals' ability to manage personal finances and make wise investment decisions. However, there are still gaps in knowledge and practice in the field that hinder the optimal use of digital financial literacy. The urgency of this activity is to strengthen digital financial literacy in the community. By understanding its influence on investment decision-making, strategies can be developed to increase awareness and understanding of digital finance, thereby helping people make more informed investment decisions. AHP was chosen due to its unique ability to handle subjective and objective preferences and the complexity of decision-making, making it very suitable for examining the phenomenon of digital financial literacy in the context of investment decision-making.